2005
DOI: 10.1111/j.1540-8183.2005.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age in the Immediate and Long‐Term Outcomes of Percutaneous Mitral Balloon Valvuloplasty

Abstract: Age is an important predictor of immediate and long-term outcomes after PMV, particularly in patients with optimal mitral valve morphology. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
7
2
Order By: Relevance
“…As a difference from previous studies which were concluded that the predictive value of combined clinical, echocardiographic, and hemodynamic parameters (7,12,14,21), we identified that only preprocedural MVA assessed by echocardiography is a significant predictor of immediate procedural results. Importantly, in the subgroup of patients with less favorable anatomy by echocardiographic score (score >8), who are often excluded from undergoing PMBV on this basis, we have shown that if PMBV performed by experienced operator, success of PMBV will be similar between patients regardless of MWS.…”
Section: Discussioncontrasting
confidence: 96%
“…As a difference from previous studies which were concluded that the predictive value of combined clinical, echocardiographic, and hemodynamic parameters (7,12,14,21), we identified that only preprocedural MVA assessed by echocardiography is a significant predictor of immediate procedural results. Importantly, in the subgroup of patients with less favorable anatomy by echocardiographic score (score >8), who are often excluded from undergoing PMBV on this basis, we have shown that if PMBV performed by experienced operator, success of PMBV will be similar between patients regardless of MWS.…”
Section: Discussioncontrasting
confidence: 96%
“…In an earlier report an ECHO score > 8 was independently related to a worse immediate result of PMBV in a large cohort [2]. In a group of 44 patients with the age ≥ 75 years procedural success was greater in patients with ECHO score £ 8 although significance level was not achieved [26]. We have not found any data from the literature indicating that pre-procedure MVG predicts PMBV result in the elderly.…”
Section: Discussioncontrasting
confidence: 65%
“…Fawzy et al, on the other hand, reported event-free survival rates at 10 and 13 years of 80 ± 3 and 74 ± 3%, respectively, in 493 patients in younger patients (mean age: 31 ± 11) [16]. Previous studies showed that age is an important factor [3,10,12,16,25,26], and, with respect to that, our study population was older than in those previous reports, and the long-term outcome seemed to be acceptable.…”
Section: Discussionmentioning
confidence: 40%